Diagnostic Test to Assess Misconceptions on Photosynthesis and Plant Respiration: Is It Valid and Reliable? (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
High percentage of secondary school students was found that they were lack of understanding of the relationship between photosynthesis and respiration in plants. They did not fully understand the importance and function about plant respiration. Thus, this study designed to develop a valid and reliable instrument in two- tier multiple choice questions format which called Photosynthesis and Plant Respiration Diagnostic Test (PRDT) to assess the common types of misconceptions related to this topic among form four students (Grade 10) in Malaysia. Survey research method was applied in this study. There were 500 participants from 15 secondary schools were involved. 45 minutes were given to the participants in answering 18 two- tier diagnostic test items. The psychometric properties of the instrument had been tested using Rasch analysis. The result found that the newly developed instrument was valid and reliable. It brought the significant contribution in teaching and learning, especially classroom assessment practice in Biology subject.